HUBUNGAN PERCAYA DIRI DENGAN PENYESUAIAN DIRI SISWA KELAS VII SMP N 1 PLANTUNGAN - Setiawan, Rusdi Anwar (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
"The Relationship of Confidence with Self-Adjustment of Students of SMP N 1 Plantungan". Thesis. Guidance and Counseling Study Program. Faculty of Science Education. UNIVERSITY PGRI Semarang. Advisor I : Dr. Yovitha Juliejaningsih, M.Pd Advisor II : Dr. G Rohastono Ajie, M.Pd.Research on the Relationship between Self-Confidence and Self-Adjustment in Class VII SMP N 1 Plantungan was motivated by the difficulty of students interacting with new friends, not knowing much about the new environment at school, feeling ashamed to interact with teachers and employees at school and solving problems with playmates. The goal to be achieved in this study is to determine the effect of self-confidence on students' self-adjustment.This type of research is quantitative research with a correlational research design. The population in this study was 120 students including VII A, VII B, VII C, VII D. The data collection technique used saturated sampling technique. All members of the population were sampled. The sample in this study used 3 classes, namely VII B, VII C and VII D.Based on the Pearson product moment correlation test, the correlation value of r arithmetic is 0.372 < r table 0.214, so it can be concluded that there is a relationship or correlation in the self-confidence variable with students' self-adjustment, the relationship between r count in this analysis is positive.